Determinants of urban violence in Lima Metropolitana and Callao: Crimes against property cases - León Mendoza, Juan (2015)
The article’s main purpose is to specify the variables that contribute to the generation of crimes against property (robberies and assaults).Currently, crime against property is the most important problem of violence and urban insecurity in the Peruvian capital and the degree of incidence tends to continue to increase.According to the results of the regressions performed, the main determinants of the generation of these crimes are: inequality in income distribution, drug use, population density and poverty. The elasticities are estimated to be 4.23, 0.20, 0.17 and -0.15 respectively.